AESTHETIC RESOLUTION WITH DIRECT FACETING IN COMPOSITE RESIN USING THE DIRECT TECHNIQUE - CASE REPORT - Cunha, Vitor Lucas Rezende; Fernandes, Gabriela Araujo; Carvalho, Ana Júlia Silva; Vilela, Ana Giulia; Santos, Gustavo Henrique; Rodrigues, Ana Laura Alves; Port, Ana Clara; Sousa, ⁠Anna Beatriz de; Borges, Daniela Borges; Melo, ⁠Maria Eduarda Soares e; Leão, Jhullia Lopes; Seabra, Kálita Cristina; et al. (CIPEEX, 2025)
The growing demand for dental procedures aimed at improving dental harmony and smiles has led to advances in materials and techniques, especially minimally invasive procedures. Any dental changes affect individuals' self-esteem and social interaction, especially tooth discoloration, which is a frequent complaint among patients seeking aesthetic solutions. Objective: To report the restoration of the aesthetics of a discolored anterior tooth using a direct composite resin veneer. Case report: The patient, MRF, female, attended the UniEVANGÉLICA Dental Clinic complaining of aesthetic dissatisfaction with a "very yellow front tooth, different from the others." Upon performing an intraoral examination, it was noticed that tooth 21 was discolored, and periapical radiography showed satisfactory endodontic treatment, with no periapical changes. A direct composite resin veneer was proposed, following the clinical protocol for composite resin restorations, using modified absolute isolation of the operative field, with excellent immediate aesthetic results. In a subsequent session, finishing and polishing completed the restorative procedure . Conclusions: With the constant improvement of composite resins and adhesive systems, direct aesthetic procedures have been performed satisfactorily, allowing the restoration of smile harmony and improving the patient's self-esteem.